(untitled) (Journal of Pharmaceutical Negative Results, 2022)
A particular kind of kidney tumor is called a renal angiomyolipoma. Nearly 80% of them are benign (non-cancerous), however they can bleed, which can be fatal. When cells grow and divide more frequently than they ought to, a tumor results. Blood arteries, muscle cells, and fat make up a renal angiomyolipoma. A rare solid tumor with benign features is the renal angiomyolipoma, commonly known as renal hematoma. Renal angiomyolipoma has an autosomal dominant inheritance pattern. A number of clinical symptoms and catastrophic consequences could happen if the lesion becomes very large. A 48-year-old female patient was admitted to the urology ward complaining of high-grade intermittent fever up to 102.4 0 F with chills, pain in lumber region since two days ago, nausea, and projectile vomiting. Patient also complaint of incontinence urine with feeling of incomplete voiding, and intermittent hematuria and these symptoms progressively got worse. After undergoing certain specific investigations like CT scan, abdominal ultrasonography, and blood investigation, the patient was diagnosed with renal angiomyolipoma. The primary therapeutic intervention was done on the patient and she was treated with Inj. Piptaz, Inj.Pantoprazole, Inj. Emset, Inj.Neomol, and intravenous fluid during hospitalization.